Joëlle Beaucamp - Françoise Briquel-Chatonnet - Christian Julien Robin (eds.): Juifs et chrétiens en Arabie au Ve et VIe siècles: regards croisés sur les sources - Kropp, Manfred (Aethiopica, 2013)
Review Article